2013
DOI: 10.2217/bmm.13.16
|View full text |Cite
|
Sign up to set email alerts
|

Length of Psychiatric Hospitalization is Correlated With CYP2D6 Functional Status in Inpatients with Major Depressive Disorder

Abstract: Aim This study aimed to determine the effect of the CYP2D6 genotype on the length of hospitalization stay for patients treated for major depressive disorder. Methods A total of 149 inpatients with a diagnosis of major depressive disorder at the Institute of Living, Hartford Hospital (CT, USA), were genotyped to detect altered alleles in the CYP2D6 gene. Prospectively defined drug metabolism indices (metabolic reserve, metabolic alteration and allele alteration) were determined quantitatively and assessed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 43 publications
(55 reference statements)
0
35
0
Order By: Relevance
“…In particular, a risperidone or venlafaxine result suggesting a PM genotype should serve as an indication for additional TDM to guide the dosing of other coprescribed drug substrates of CYP2D6 so as to avoid the risk of adverse drug reactions as reported in several clinical settings. [2][3][4][5][6][7] Thus, genetically deficient CYP2D6 metabolism has been associated with adverse drug reactions in patients treated with CYP2D6-dependent antidepressants, 2 with a greater length of hospitalization for different groups of psychiatric patients, 4,5 with prolonged QTc interval in patients on risperidone, 3 and with extrapyramidal syndrome or tardive dyskinesia in patients taking antipsychotic drugs in general. 6,7 Importantly, such a strategy would also avoid therapeutic failure with regard to prodrugs, ie, drugs whose therapeutic effect is dependent on a pharmacologic active metabolite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, a risperidone or venlafaxine result suggesting a PM genotype should serve as an indication for additional TDM to guide the dosing of other coprescribed drug substrates of CYP2D6 so as to avoid the risk of adverse drug reactions as reported in several clinical settings. [2][3][4][5][6][7] Thus, genetically deficient CYP2D6 metabolism has been associated with adverse drug reactions in patients treated with CYP2D6-dependent antidepressants, 2 with a greater length of hospitalization for different groups of psychiatric patients, 4,5 with prolonged QTc interval in patients on risperidone, 3 and with extrapyramidal syndrome or tardive dyskinesia in patients taking antipsychotic drugs in general. 6,7 Importantly, such a strategy would also avoid therapeutic failure with regard to prodrugs, ie, drugs whose therapeutic effect is dependent on a pharmacologic active metabolite.…”
Section: Discussionmentioning
confidence: 99%
“…Different genetic variants of CYP2D6 indeed contribute to marked interpatient variability in their pharmacokinetics, 1 with a well established impact on the clinical outcome and, in particular, the risk of adverse events with regard to drugs metabolized by this enzyme. [2][3][4][5][6][7] However, in most institutions, CYP2D6 genotyping has not been adopted into routine clinical practice, instead it has been restricted to retrospective analyses in selected cases. 8 Knowledge of the individual CYP2D6 activity, or more specifically the poor metabolizer (PM) or ultrarapid metabolizer (UM) genotype, is of potential importance regarding ongoing and future drug treatment in patients with many antidepressants and antipsychotics.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of genes are likely to influence the toxicity and response of an individual medication of antidepressant response [1][2][3][4][5][6][7][8][9][10][11][12][13][14]15]. A recent study focused on determination of the effect of the CYP2D6 genotype on the length of hospitalization stay for patients treated for major depressive disorder and found that the hospital stay was significantly longer in deficient CYP2D6 metabolizers compared with functional or supra-functional metabolizers [16]. Importantly, Federal agencies, including the Department of Health and Human Services and the US Food and Drug Administration (FDA) are incorporating pharmacogenomics dosing guidance into the labelling, development, and approval of drugs in a manner that supports gene-based care in more than 110 medications.…”
Section: Current Findingsmentioning
confidence: 99%
“…The recently published paper by Ruaño et al [1] addresses an urgent need for evidence-based clinical applications of CYP2D6 pharmaco-genomics in the area of psychiatry, in this case in the potential impact on a clinically relevant complex outcome (i.e., length of hospitalization stay [LOS]) of pharmacogenetic testing for guiding therapy of psychiatric inpatients with major depressive disorders at a mental health institution in the New England (CT, USA) area. In doing so, the authors computed a prospectively defined ‘drug metabolic reserve’ index for each participant, based on individual CYP2D6 genotypes, to infer their innate metabolic capacity through this enzymatic pathway, and then tested whether an association with the LOS was observed.…”
mentioning
confidence: 99%
“…Their findings are relevant insofar as they provide a functional scoring of CYP2D6 carrier status with a potential impact on the quality of care, patient satisfaction and the utilization of healthcare resources in psychiatry, as well as other pharmacoeconomic issues related to an optimal therapeutic management strategy. Notably, those functionally deficient patients (CYP2D6 metabolic reserve <2; n = 66) clearly segregated from the rest to show a longer LOS, and were also more likely to have an extended time on therapy with a psychiatric drug [1]. In fact, the CYP2D6 metabolic reserve index alone accounted for approximately 6% of the observed variability in the LOS after regression analysis.…”
mentioning
confidence: 99%